The modern methods of using games in teaching foreign language. (Journal of Universal Science Research, 2023)
This article discusses the benefits and unique methods of using innovative technology in teaching the English language. Throughout the article, various new and modern types of innovative technology are presented, along with specific ways to utilize them. The article concludes with scientific conclusions and thoughts.